Diabetic macular oedema: clinical risk factors and emerging genetic influences. (26th May 2017) - Liu, Ebony; Craig, Jamie E; Burdon, Kathryn
Abstract : Diabetic macular oedema is the major cause of visual impairment in type 1 and type 2 diabetes. As type 2 diabetes becomes more prevalent worldwide, the prevalence of diabetic macular oedema is also expected to rise. Current management of diabetic macular oedema is challenging, expensive and not optimal in a subset of patients. Therefore, it is important to increase our understanding of the risk factors involved and develop preventative strategies. While clinical risk factors for diabetic macular oedema have been identified, few studies have addressed potential genetic risk factors. Epidemiology and family studies suggest genetic influences are of importance. In this review, we summarise known clinical risk factors, as well as discuss the small number of genetic studies that have been performed for diabetic macular oedema.